Myth and Reality of University Museum as an Information Resource Center in State Islamic Universities - Pungki Purnomo (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2018)
This study discusses the phenomenon of university museum which is rarely studied particularly in State Islamic Universities. The objective of this study is to reveal the opportunities and challenges of State Islamic Universities in establishing the university museum as an information resource centers for academicians. This research was conducted at four different State Islamic Universities (UIN) in Indonesia such as Jakarta, Surabaya, Jogjakarta and Malang. The method used in this study was qualitative with a phenomenological approach. The informants in this study were lecturers and librarians. The opportunities for establishment of a university museum in UIN are : firstly, some departments offer courses that require a laboratory with object-based learning. Secondly : is UIN lecturersare relatively expertise. Likewise, the trust of UIN partners is very strong and entrenched both at home and abroad. The last one is that each UIN even has the potential opportunity to be able to develop a university museum that is distinct from the other universities in its Islamic themes. The challenges include that the position of university museum has not been regulated in the UIN statute. Moreover, the political will of university leaders, lecturers and students on the importance of a university museum still has not become common wish as a center of information resources.